THE IMPLEMENTATION OF HYBRID LEARNING STRATEGY TO IMPROVE STUDENTS' LEARNING OUTCOMES AT SMA 1 SERAM BAGIAN BARAT - Saulatu, R. Hidayat (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to improve students' learning outcomes through the implementation of the Hybrid Learning strategy for 30 students at SMA Negeri 1 Seram Bagian Barat. This research is a classroom action research consisting of four stages: action planning, action implementation, evaluation, and reflection. The study was conducted in two cycles — Cycle I consisted of three meetings, while Cycle II consisted of two meetings. Data were collected through observation sheets, tests, Zoom Meeting applications, and documentation. The data analysis technique used was descriptive statistical analysis. The findings of this study indicate that the implementation of the Hybrid Learning strategy can improve students' learning outcomes. This is evidenced by the increase in students' learning scores from Cycle I to Cycle II.